Muscle Free Fatty-Acid Uptake Associates to Mechanical Efficiency During Exercise in Humans - Laaksonen, Marko S.; Kyröläinen, Heikki; Kemppainen, Jukka; Knuuti, Juhani; Kalliokoski, Kari K. (Frontiers in Physiology, 2018)
Intrinsic factors related to muscle metabolism may explain the differences in mechanical efficiency (ME) during exercise. Therefore, this study aimed to investigate the relationship between muscle metabolism and ME. Totally 17 healthy recreationally active male subjects were recruited and divided into efficient (EF; n=8) and inefficient (IE; n=9) groups, which were matched for age (mean±SD 24±2 vs. 23±2 yrs), BMI (23±1 vs. 23±2 kg m-2), physical acitivity levels (3.4±1.0 vs. 4.1±1.0 sessions/week), and V ̇O2peak (53±3 vs. 52±3 mL kg-1 min-1), respectively, but differed for ME at 45% of VO2peak intensity during submaximal bicycle ergometer test (EF 20.5±3.5 vs. IE 15.4±0.8 %, P < 0.001). Using Positron Emission Tomography, muscle blood flow (BF) and uptakes of oxygen (mVO2), fatty acids (FAU) and glucose (GU) were measured during dynamic submaximal knee-extension exercise. Workload-normalized BF (EF 35±14 vs. IE 34±11 mL 100g-1 min-1, P = 0.896), mVO2 (EF 4.1±1.2 vs. IE 3.9±1.2 mL 100g-1 min-1, P = 0.808), and GU (EF 3.1±1.8 vs. IE 2.6±2.3 μmol 100g-1 min-1, P = 0.641) as well as the delivery of oxygen, glucose, and fatty acids, as well as respiratory quotient were not different between the groups. However, FAU was significantly higher in EF than IE (3.1±1.7 vs. 1.7±0.6 μmol 100g-1 min-1, P < 0.047) and it also correlated with ME (r=0.56, P < 0.024) in the entire study group. EF group also demonstrated higher use of plasma fatty acids than IE, but no differences in use of plasma glucose and intramuscular energy sources were observed between the groups. These findings suggest that the effective use of plasma fatty acids is an important determinant of mechanical efficiency during exercise.